Alternative energy technologies an introduction with computer simulations - Buxton, Gavin (Gavin Alan) (Nano and energy series, 2015)
Alternative energy sources are becoming increasingly important in a world striving for energy independence, clean air, and a reprieve from global warming. Solar cells, wind power, and biofuels are some of the competing alternative energy sources hoping to gain a foothold in our future energy mix, and the economic advantages of these technologies are continually increasing as costs are reduced and efficiencies increased. Alternative Energy Technologies: An Introduction with Computer Simulations explores the science and engineering behind a number of emerging alternative energy technologies, including polymer solar cells, algae biofuels, and artificial leaves.